From the good mountain : how Gutenberg changed the world - Rumford, James, 1948- (New York : Flash Point, 2012)
Describes how Johann Gutenberg's printing press changed the world and how early books were printed.
"A Neal Porter book."
Booklist
Publisher's Weekly
School Library Journal starred
Booklist, August 2012
Kirkus Review, August 2012
Keywords: Gutenberg, Johann, -- 1397?-1468 -- Juvenile literature; Gutenberg, Johann, -- 1397?-1468.; Gutenberg, Johann, -- 1397?-1468.; Books -- History -- Juvenile literature; Printers -- Germany -- Juvenile literature; Printing -- History -- Origin and antecedents -- Juvenile literature; Books -- History; Printers -- Germany; Printing -- History -- Origin and antecedents; Books -- History; Printers; Printing -- History -- Origin; Picture books for children